Cover, Table of Contents, and Editorial Note – Vol. 14 No. 1 (2025) - Ahmad Mukhlasin (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This file contains the journal cover, table of contents, and the editorial note from the Editor in Chief for Volume 14, Issue 1 (2025). These components serve as the opening elements of the journal edition and reflect the overarching theme and editorial perspective of this issue.